Cutaneous Neuroendocrine Carcinoma of the External Auditory Canal: A Case Report and Review of the Literature. (5th August 2012) - Li, Yi-Ke; Chi, Fang-Lu; Wang, Shu-Yi; Wang, Wu-Qing; Yang, Juan-Mei; Huang, Yi-Bo
Abstract : Cutaneous neuroendocrine carcinoma (cNEC) is rarely seen in the external ear. In this paper, we newly describe a patient with cNEC in his right external auditory canal, followed by a further discussion on the clinical features, diagnosis, and treatments of cNEC of the external ear. A review of the literature showed that cNEC of the external auditory canal generally presents as asymptomatic and that pathology yields the most confirmative diagnosis. A wide resection with adjuvant radiotherapy and chemotherapy is recommended. The overall prognosis of this condition is poor.